Landscapes. Territories, Frontiers and Horizons in the Ancient Near East. Papers presented to the XLIV Rencontre Assyriologique Internationale, Venezia, 7-11 July 1997. Part II: Geography and Cultural Landscapes - Fales, Frederick Mario; Martino, Stefano de; Milano, Lucio (2000)
= RAI 44/II